Kinerja Pra-Produksi, Proses Produksi, dan Pasca Produksi Tentang Radio Dalam Manajemen Siaran Dakwah - Efendi, Erwan; Badriah, Ainun; Nurbaiti, Nurbaiti; Hasanah, Putri (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
Da'wah is an activity to invite people to commendable activities and also keep away from those that are reprehensible. Da'wah activities can be carried out in various ways, either orally or in writing. along with the development of the times da'wah also utilizes existing media such as radio. Radio is one of the communication media that is relevant for carrying out da'wah activities. In addition, radio is also an auditive medium through the ear and also hearing, as a means of radio communication, of course, it provides benefits for the community, especially for preachers to carry out their preaching management to the community. Broadcasting of the Islamic religion carried out via radio certainly has its own advantages, this is because radio is audio in nature so that listeners can directly listen to the material conveyed by the preacher. To get good results, a planned process is also needed starting from production preparation to the completion of the event. Keywords: Performance, radio production, management of da'wah broadcasts